Illustrated tips and tricks in sports medicine surgery - Azar, Frederick M. (Illustrated tips and tricks series., 2019)
"Publisher's Note: Products purchased from 3rd Party sellers are not guaranteed by the Publisher for quality, authenticity, or access to any online entitlements included with the product. This new quick-reference is the latest volume in the Illustrated Tips and Tricks series. You'll find succinct, precise information from a wide range of experts and prestigious institutions on tackling technical problems in sports medicine surgery. Drawings, operative photos, and videos are used liberally throughout the book to illustrate surgical techniques and provide a handy visual complement to the text. Features the latest surgical techniques, presented in a crisp, step-by-step style, and provides brief overviews of equipment, anesthesia, patient positioning, and other procedural elements. Designed for residents, fellows, and practicing orthopaedists--those in training or anyone who needs to brush up on the latest techniques. Covers common treatments for addressing bone and tendon injuries of the shoulder, elbow, hip, knee, foot, and ankle. Numerous figures, precisely drawn to minute detail, pack each chapter. Concise, bulleted format makes for easy reading and quick absorption of material. Enrich Your eBook Reading Experience with Enhanced Video, Audio and Interactive Capabilities! Read directly on your preferred device(s), such as computer, tablet, or smartphone. Easily convert to audiobook, powering your content with natural language text-to-speech. Adapt for unique reading needs, supporting learning disabilities, visual/auditory impairments, second-language or literacy challenges, and more"--